Single nucleotide polymorphisms in vitamin D binding protein and 25-hydroxylase genes affect vitamin D levels in adolescents of Arab ethnicity in Kuwait - Rahman, Abdur; Abu-Farha, Mohamed; Channanath, Arshad; Hammad, Maha M.; Anoop, Emil; Chandy, Betty; Melhem, Motasem; Al-Mulla, Fahd; Thanaraj, Thangavel Alphonse; Abubaker, Jehad (Frontiers in Endocrinology, 2023)
Vitamin D deficiency (VDD) is widespread in the Arab world despite ample sunshine throughout the year. In our previous study, lifestyle and socio-demographic factors could explain only 45% of variability in vitamin D levels in Kuwaiti adolescents, suggesting that genetics might contribute to VDD in this region. Single nucleotide polymorphisms (SNP) in the 25-hydroxylase (CYP2R1) and the GC globulin (GC) genes have been reported to affect vitamin D levels in various ethnic groups in adults. In this study, we investigated the association of two SNPs from GC (rs4588 and rs7041) and three SNPs from CYP2R1 (rs10741657, rs11023374 and rs12794714) with vitamin D levels and VDD in a nationally representative sample of adolescents of Arab ethnicity from Kuwait. Multivariable linear regression, corrected for age, sex, parental education, governorate, body mass index, and exposure to sun, demonstrated that each of the 5 study variants showed significant associations with plasma 25(OH)D levels in one or more of the additive, recessive, and dominant genetic models - the rs10741657 under all the three models, rs12794714 under both the additive and recessive models, rs7041 under the recessive model; and rs4588 and rs11023374 under the dominant model. Minor alleles at rs4588 (T), rs7041 (A), rs11023374 (C), and rs12794714 (A) led to a decrease in plasma 25(OH)D levels - rs4588:[β (95%CI) = -4.522 (-8.66,-0.38); p=0.033]; rs7041:[β (95%CI) = -6.139 (-11.12,-1.15); p=0.016]; rs11023374:[β (95%CI) = -4.296 (-8.18,-0.40); p=0.031]; and rs12794714:[β (95%CI) = -3.498 (-6.27,-0.72); p=0.014]. Minor allele A at rs10741657 was associated with higher levels of plasma 25(OH)D levels [β (95%CI) = 4.844 (1.62,8.06); p=0.003)] and lower odds of vitamin D deficiency (OR 0.40; p=0.002). These results suggest that the CYP2R1 and GC SNP variants are partly responsible for the high prevalence of VDD in Kuwait. Genotyping these variants may be considered for the prognosis of VDD in Kuwait.